Diabetes mellitus and hepatitis c in generalised lichen planus: a case control study - Parimalam, K.; Sowmiya, R.; Mithra, S. (International Journal of Research in Dermatology, 2019)
Background: Prevalence of lichen planus (LP) and generalised lichen planus (GLP) is about 2.6% and 1% respectively. Various studies have shown higher prevalence of Diabetes Mellitus (DM) and stronger association between Hepatitis-C virus (HCV) and LP. The main objective of this study was to predict the prevalence of DM and HCV in patients with GLP before starting steroids. Methods: A case-control study was conducted with 33 patients in each group for one year period. Case group included patients with GLP excluding oral LP and drug induced lichenoid dermatitis. Control group included patients with other skin conditions and not on steroids. Preliminary details and history of DM and HCV were collected. Random blood sugar and Anti-HCV were done. Results: The proportion of patients with GLP was higher in women compared to men (63.6% vs. 36.3%). Highest prevalence was observed in the age group 35-45 years for both genders. On stratification by sex, odds of having GLP in women are 0.76 times lower among diabetics compared to non-diabetics whereas no association in males. There was no association between GLP and HCV in both sexes. Conclusions: There is no significant association between Diabetes mellitus and Hepatitis-C infection with GLP. Future study is planned with larger sample size for a definite conclusion.